1986
DOI: 10.1016/0020-711x(86)90075-3
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin biosynthesis in rhodopseudomonas palustris—V. Purification of porphyrinogen decarboxylase and some unusual properties

Abstract: A~tract--Uroporphyrinogen decarboxylase (EC 4.1.1.37) has been purified 16-fold from Rp. palustr• to a specific activity of 210 nmol of total decarboxylated porphyrinogens III formed/hr per mg of protein and about 50% yield. The Rp. palustris enzyme exhibits some unusual properties as compared with URO-D from other sources.2. The purified enzyme is a monomer with a molecular weight of ~46,000, an isoelectric point of 4.6 and an optimum pH of 6.9 and 6.8 with urogen III and I substrate. Neither GSH nor EDTA see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…This is the first time that UroD activity has been studied in a green algae (Chlorella). The chromatographic profile of the reaction products is similar to that of UroD from other sources, such as rat liver (Ríos de Molina et al 1987), bacteria (Koopmann et al 1986), and Euglena gracilis (Juknat et al 1989). Moreover, this profile shows the prevalence of 7 COOH over 6 and 5 COOH intermediates, suggesting that 7 COOH porphyrinogen decarboxylation is the rate-limiting step in C. kessleri UroD reaction, as reported for rat and bovine liver (Straka and Kushner 1983;Ríos de Molina et al 1987), avian erythrocytes (García et al 1973), and bacteria (Koopmann et al 1986)…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This is the first time that UroD activity has been studied in a green algae (Chlorella). The chromatographic profile of the reaction products is similar to that of UroD from other sources, such as rat liver (Ríos de Molina et al 1987), bacteria (Koopmann et al 1986), and Euglena gracilis (Juknat et al 1989). Moreover, this profile shows the prevalence of 7 COOH over 6 and 5 COOH intermediates, suggesting that 7 COOH porphyrinogen decarboxylation is the rate-limiting step in C. kessleri UroD reaction, as reported for rat and bovine liver (Straka and Kushner 1983;Ríos de Molina et al 1987), avian erythrocytes (García et al 1973), and bacteria (Koopmann et al 1986)…”
Section: Discussionsupporting
confidence: 75%
“…During the first stage, the rapid decarboxylation of Urogen III (8 COOH) yields a 7 COOH compound. During the second, the other 3 COOH groups are sequentially eliminated yielding coproporphyrinogen III (Coprogen III, 4 COOH) through the formation of 6 and 5 COOH porphyrinogen intermediates (Jackson et al 1976; Koopmann et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of heat upon activity are similar to those made on the uroporphyrinogen decarboxylases from human erythrocytes (Elder et al, 1983;de Verneuil et al, 1983a). In contrast, the uroporphyrinogen decarboxylase partially purified from R. palustrus (Koopmann et al, 1986) was reported to be heat stable and this property was exploited during its partial purification.…”
Section: Determination Of the Ph Optimum And Isoelectric Point Of Uromentioning
confidence: 75%
“…Previously published methods describe only the partial purification of the enzyme from R. sphaeroides (Hoare and Heath, 1959) and R. palustrus (Koopmann et al, 1986). The purification procedure described in this paper gives homogeneous uroporphyrinogen decarboxylase from R. sphaeroides, with a 600-fold purification overall (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation